Jornadas De Esterilización Masivas Gratuitas Y A Bajo Costo Realizadas Durante La Pasantía En Clínicas Veterinarias De Bogotá Y Soacha” (2025)
This degree work was developed under the internship modality through free and low massive sterilization days held in veterinary clinics in Bogotá and Soacha becoming a great experience since it was possible to reinforce and apply knowledge acquired throughout the career through the accompaniment of professionals. In total, 26 days were participated in, attending 1.058 feline and canine pets. The largest numbers of surgeries were performed on female felines and female canines with 686 patients operated on in relation to the 372 males of both species. Among the participating entities (two private and one public), the public entity attended to 640 furry animals.